Dinamika Kelembagaan Dalam Pelekasana Otonomi Khusus Syariat Islam Di Aceh (Kajian Kelembagaan) - Helmi Helmi; Achmad Nurmandi (Universitas Muhammadiyah Yogyakarta, 2016)
This study wants to answer how the Institutional dynamics in the implementation of special autonomy in the field ofIslamic Law in Aceh that have not effective and efficient so it is necessary for the agency's role maximizing theoverall implementation of Islamic Law in Aceh through regulatory quality and the quantity produced by the agencyqanun the quality of the actors in the bureaucracy, institutional partnership and good governance can demonstratesuccess in implementing the task, purpose this study was to examine more deeply about the institutional, inimplementing special autonomy in the field of Islamic Law in Aceh, three pillar theory, namely; Regulative, normativeand Culture / Cognitive, the data in the study This is obtained from the three agencies and the non-governmentalorganizations and 70 respondents in organizations that have a working partner and responsibility towardsimplementation of Islamic Law in Aceh. The method used in this research is mixed method research methods. Datacollection techniques used is library research, interviews, documents and questionnaires. The findings in this studythat first; the success of implementing Shari'a second; cultural influences and bigotry Aceh society against theteachings of Islam so that Islam be cultural identity and sense of self-esteem, even Aceh society people unitereligion with the culture and customs that can not be separated, third; tolerance towards non-Muslims, and thuscreating feel safe and comfortable in the religion of the minorities in Aceh. And Fourth; dialectic role of scholarsbetween structures and actors, where public Aceh is also obedient and trust theologian, not only on the structureand regulative, normative institution.